Underground ventilation : proceedings of the 19th North American Mine Ventilation Symposium (NAMVS 2023, 17-22 June 2023, Rapid City, South Dakota, USA) /: proceedings of the 19th North American Mine Ventilation Symposium (NAMVS 2023, 17-22 June 2023, Rapid City, South Dakota, USA). (2023) - Unknown
No abstract available